Strategic Management Practices and their Relevance to Making Strategic Decisions: The Aspect of Small and Medium Enterprises in Yemen - Mugaahed Abdu Kaid Saleh; Manjunath K. R (Journal of North African Economies, 2025)
The ability to understand modern management practices and techniques and apply them effectively is one of the keys to successful management, and knowledge about past and present models and theories is crucial for managers. This paper attempts to investigate strategic managerial practices with their relevance to making sound strategic decisions among manufacturing SMEs in Yemen. The study is a cross-sectional study that relied on primary data collected conveniently from 400 owners and managers of manufacturing SMEs in Yemen. The findings show low levels of adopting strategic management practices among manufacturing SMEs and a significant role of the scope of operation in differentiating the adoption of such practices. The study recommends increasing the attention towards supporting and encouraging managers and owners of SMEs to further embrace strategic practices while making decisions to march towards development and sustainability.